Infections among Contacts of Patients with Nipah Virus, India - Kumar, C.P. Girish (Emerg Infect Dis, 2019)
We conducted a serosurvey of 155 healthcare workers and 124 household and community members who had close contact with 18 patients who had laboratory-confirmed Nipah virus infections in Kerala, India. We detected 3 subclinical infections; 2 persons had IgM and IgG and 1 only IgM against Nipah virus.